A Qualitative Study of the Change-of-Shift Report at the Patients' Bedside. Issue 4 (October 2016) - Grimshaw, John; Hatch, Daniel; Willard, Melissa; Abraham, Sam
Abstract : Concerns about patient bedside change-of-shift reporting at a community hospital in northern Indiana stimulated the development of this qualitative phenomenological study. A review of the literature revealed a research deficit in acute care nurses' perceptions of bedside reporting in relation to compliance. The research question addressed in this study was, "What are acute care nurses' perceptions of the change-of-shift report at the patients' bedside?" Personal interviews were conducted on 7 medical, surgical, and intensive care unit nurse participants at a community hospital in northern Indiana. Five themes were identified from the collected data, which included the time factor, continuity of care, visualization, and challenges in the communication of discreet information.